Hepatocyte KLF6 expression affects FXR signalling and the clinical course of primary sclerosing cholangitis. (28th June 2020) - Sydor, Svenja; Manka, Paul; van Buren, Lea; Theurer, Sarah; Schwertheim, Suzan; Best, Jan; Heegsma, Janette; Saeed, Ali; Vetter, Diana; Schlattjan, Martin; Dittrich, Anna; Fiel, Maria I.; et al.
Abstract: Background & Aims: Primary sclerosing cholangitis (PSC) is characterized by chronic cholestasis and inflammation, which promotes cirrhosis and an increased risk of cholangiocellular carcinoma (CCA). The transcription factor Krueppel‐like‐factor‐6 (KLF6) is a mediator of liver regeneration, steatosis, and hepatocellular carcinoma (HCC), but no data are yet available on its potential role in cholestasis. Here, we aimed to identify the impact of hepatic KLF6 expression on cholestatic liver injury and PSC and identify potential effects on farnesoid‐X‐receptor (FXR) signalling. Methods: Hepatocellular KLF6 expression was quantified by immunohistochemistry (IHC) in liver biopsies of PSC patients and correlated with serum parameters and clinical outcome. Liver injury was analysed in hepatocyte‐specific Klf6 ‐knockout mice following bile duct ligation (BDL). Chromatin‐immunoprecipitation‐assays (ChIP) and KLF6‐overexpressing HepG2 cells were used to analyse the interaction of KLF6 and FXR target genes such as NR0B2. Results: Based on IHC, PSC patients could be subdivided into two groups showing either low (<80%) or high (>80%) hepatocellular KLF6 expression. In patients with high KLF6 expression, we observed a superior survival in Kaplan‐Meier analysis. Klf6 ‐knockout mice showed reduced hepatic necrosis following BDL when compared to controls. KLF6 suppressed NR0B2 expression in HepG2 cells mediated through binding of KLF6 to the NR0B2 promoter region. Conclusion: Here, we show an association between KLF6 expression and the clinical course and overall survival in PSC patients. Mechanistically, we identified a direct interaction of KLF6 with the FXR target gene NR0B2 .